PENERAPAN METODE FUZZY SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS UNTUK PENGUKURAN KEPUASAN MAHASISWA TERHADAP KUALITAS LAYANAN PORTAL INSPIRE UNSRAT - Neyland, Johan S.C.; Mende, Jefferson; Mawikere, Lidia M. (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract The purpose of this research is to measure student satisfaction with the information provided by the Unsrat Inspire portal service using fuzzy servqual and Importance Performance Analysis (IPA) methods by conducting surveys through questionnaires. The stages of this research are starting from studying existing literature to become the basis for taking questionnaires, processing data to drawing conclusions. From the results of the study, it was found that all statement attributes gave negative values, although not too large, which meant that students were still not satisfied with the inspire portal service. It can be seen from the table that the top five that get the biggest negative value are the security of student data on the Unsrat Inspire Portal (-0.57), the accuracy of announcement information on the Unsrat Inspire Portal (-0.57), making it easier for students to find exam schedules (-0.48), the accuracy of lecturer information provided to students through the Unsrat Inspire Portal (-0.46), and the features on the Unsrat Inspire Portal are complete (-0.45) while from the Importance & Performance Analysis diagram there are 2 service attributes that are in quadrant I which means that these attributes must improve their services. Keywords: Inspire portal, integrated information system, fuzzy servqual, Important Performance Analysis.